Regional dynamics of innovation investigating the co-evolution of patents, R&D, and employment - Matthias Bürger; Tom Brökel; Alex Coad (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
We investigate the lead-lag relationship between growth of patent applications, growth of R&D, and growth of total sectoral employment for 270 German labour market regions over the period 1999-2005. Our unique panel dataset includes information on four two-digit industries, namely Chemistry, Transport equipment, Medical & Optical Equipment as well as Electrics & Electronics. The results obtained from a vector autoregression model show that an increased innovative activity is associated with subsequent growth of employment in the Medical & Optical Equipment industry as well as in the Electrics & Electronics sector. With respect to the latter growth of patent applications is also associated with subsequent growth of R&D employees indicating either a ‘success-breeds-success’ story or benefits due to agglomeration economies at the level of the region. However we do not find those effects for the other industries due to their idiosyncratic innovation and patenting behaviour.
Keywords: O18; R11; 330; Innovation; Agglomeration; Employment; Regionale Entwicklung; Industrielle Forschung; Patent; Innovation; Beschäftigungseffekt; Agglomerationseffekt; Regionaler Arbeitsmarkt; Deutschland